The Role of the United States in the War against Terrorism: An Analysis of the Syrian Crisis - Rosenje , Musharafa Olapeju; Omojowo, Toyin Sunday (Kashere Journal of Politics and International Relations, 2023)
Terrorism has become a multifaceted monster that has continued to ravage the globe. The situation in Africa and Middle East, particularly in Syria, which is presently regarded as the hotbed of terrorism, is precarious. Syria remains a terror-ridden nation due to the manifest presence and characteristic ruthlessness of many terrorist groups, prominent among which is the Islamic State of Iraq and Syria (ISIS) that is in control of one-third of Syrian territories. This article examined the role of the United States in the war against terrorism with a specific focus on the situation in Syria between 2011 and 2022. It adopted the descriptive research method, while the humanitarian interventionist theory was used as its theoretical underpinning. It revealed that the series of terrible attacks executed by these terrorist groups have led to loss of lives and properties, and resulted in the emergence of the biggest humanitarian crisis ever in Syria. It discovered that this challenge has led to the intervention of the United States with a view to decimating the threats through airstrikes and ground operations that killed several terrorist leaders and militants. It recommended that the United States must intensify strict financial control measures; improve the justice system to fast track judicial reviews and prosecution processes of terrorism provocateurs. It also recommended that the United States should involve more allies, especially in and around Syria by providing cognate counter intelligence and supplies.